Neurocognition and Social Cognition— Possibilities for Diagnosis and Treatment in Ultra-High Risk for Psychosis State - Rek-Owodziń, Katarzyna; Tyburski, Ernest; Waszczuk, Katarzyna; Samochowiec, Jerzy; Mak, Monika (Frontiers in Psychiatry, 2021)
In recent decades, clinicians have developed the construct of ultra-high risk (UHR) for psychosis to characterize the prodromal phase of psychosis or classify people with weakly expressed psychotic symptoms. In this conceptual analysis, we have gathered up-to-date data about the clinical picture of neurocognition and social cognition in people at UHR for psychosis. We also discuss treatment options. A well-chosen therapeutic approach can help to deal with difficulties and delay or even prevent the development of full-blown psychotic disorders in the UHR group. Despite much evidence supporting the benefits of therapy, early interventions are still not as widely used as they should be. Thus, a better understanding of the UHR state is very important for all healthcare workers.